Assisted Evaluation Method as Periodic Medical Control for Professional and Regular Drivers - BRAUN Barbu Criatian; DRUGĂ Corneliu Nicolae (MEDITECH 2022, Cluj-Napoca, published in SPRINGERLINK, 2022)
The paper describes how a revolutionary method was proposed, developed and tested regarding the assisted testing of the visual function in the case of drivers, within the procedures of periodic medical control. The main purpose of the method is to ensure a much more efficient and objective medical control than current methods. Another advantage would be that the method could help the examiner, being clear and easy to apply. At the same time, the objectivity of the assisted procedure could drastically reduce fraud situations. Until now, researches have focused on the aspect of medical control from the point of view of visual function, but in the future they will also expand to other aspects related to periodic medical control (pulmonary function, auditory function, locomotor function, etc.). Specifically, the method consists of a staged test of the visual function from all points of view (acuity, 3D perception, chromatic perception, visual field, etc.), it being intended for both regular and professional drivers. The basis of the assisted assessment procedure was the design, programming, testing and continuous improvement of a software interface, presented as a virtual instrument within the reach of optometrists and specific medical personnel.
Keywords: Evaluation; Visual Function; Interface; Testing; Medical Control